FaÊ¿Äliyyah IstikhdÄm Barmajah Educandy fÄ« TaÊ¿lÄ«m al-MufradÄt fÄ« al-Madrasah al-Thanawiyyah al-IslÄmiyyah al-á¸¤ukÅ«miyyah Sorong - Yunita, Syarah; Raswan, Raswan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study aimed to reveal the use of Educandy application in teaching vocabulary and analyze the effectiveness of using the application. Researchers used a experimental method with quasi-experimental research. The population is all ten grade students in Senior Islamic High School in Sorong. The students of ten grade E-3 and E-2 as the sample of the research were chosen for the experimental class and the control class. Data collection technique used in this research is test; pre-test and post-test. This study adopted T-test analysis to analyze the effectiveness of the apllication based on pre-test and post-test data. The result of the statistical calculation showed that t0 (t-value) was higher than the tt (1,99 < 5,71 > 2,65). Based on these finding, it can be said that the use of Educandy application effective in teaching vocabulary.ÙŠØ³ØªÙ†Ø¯ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ø§Ù„ØªÙŠ ÙŠÙˆØ§Ø¬Ù‡Ù‡Ø§ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø¹Ù†Ø¯ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. ÙˆØ¬Ø¯Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø£Ù† Ù‚Ø¯Ø±Ø© Ø§Ù„Ø·Ù„Ø§Ø¨ Ø¹Ù„Ù‰ ØÙØ¸ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª ÙˆÙ…Ø¹Ù†Ø§Ù‡Ø§ ÙˆÙÙ‡Ù…Ù‡Ø§ ÙˆØªØ·Ø¨ÙŠÙ‚Ù‡Ø§ ÙÙŠ Ø§Ù„ØÙŠØ§Ø© Ø§Ù„ÙŠÙˆÙ…ÙŠØ© Ø¶Ø¹ÙŠÙØ©. ÙˆØ³Ø¨Ø¨ Ø°Ù„Ùƒ Ø£Ù† Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© ØºÙŠØ± Ù…Ù†Ø§Ø³Ø¨ ÙˆØ·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¯Ø±ÙŠØ³ Ø§Ù„ØªÙŠ Ø§ØªØ¨Ø¹Ù‡Ø§ ÙÙŠ Ø§Ù„ÙØµÙ„ ØºÙŠØ± ÙØ¹Ø§Ù„Ø© ÙˆØºÙŠØ± Ù…Ù…ØªØ¹Ø©.ÙˆØ§Ù„Ù‡Ø¯Ù Ù…Ù† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø§Ù„ÙƒØ´Ù Ø¹Ù† Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø¨Ø±Ù…Ø¬Ø© Ø¥ÙŠØ¯ÙˆØ¬Ø§Ù†Ø¯ÙŠ educandy ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙØ±Ø¯Ø§ØªØŒ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø§Ø®ØªÙ„Ø§Ù ÙÙŠ Ù‚Ø¯Ø±Ø© Ø§Ù„Ø·Ù„Ø§Ø¨ Ø¹Ù„Ù‰ ØÙØ¸ Ùˆ ÙÙ‡Ù… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ù‚Ø¨Ù„ Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø¨Ø±Ù…Ø¬Ø© Ø¥ÙŠØ¯ÙˆØ¬Ø§Ù†Ø¯ÙŠ ÙˆØ¨Ø¹Ø¯ Ø§Ø³ØªØ®Ø¯Ø§Ù…Ù‡Ø§ØŒ ÙˆØ§Ù„ÙƒØ´Ù Ø¹Ù† ÙØ¹Ø§Ù„ÙŠØ© Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù‡Ø°Ù‡ Â Ø§Ù„Ø¨Ø±Ù…Ø¬Ø© ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª.Ø§Ø³ØªØ®Ø¯Ù…Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø§Ù„Ù…Ø¯Ø®Ù„ Ø§Ù„ÙƒÙ…ÙŠ Ø¨Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ Ù…Ù† Ø¯Ø±Ø§Ø³Ø© Ø´Ø¨Ù‡ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠØ©. ÙˆÙ…Ø¬ØªÙ…Ø¹ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„Ø¹Ø§Ø´Ø± ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø³ÙˆØ±ÙˆÙ†Ø¬ Ù…Ù† Ø¹Ø¯Ø¯ 284 Ø·Ø§Ù„Ø¨Ø§ØŒ ÙˆØ§Ù„Ø¹ÙŠÙ†Ø© Ù…Ù† Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„Ø¹Ø§Ø´Ø±